Standardization Of The Recipe For Randang Belut In Nagari Koto Tangah Simalanggang Payakumbuh City - Siska Indah Putri; Anni Faridah (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The quality of the eel rendang found is still varied, this is due to the absence of a standard eel rendang recipe.The purpose of this study was to obtain the most delicious and preferred eel rendang recipe.The community is expected to be able to process eel rendang by getting the same results and taste.This type of research is a mixed method,which is a combination of qualitative and quantitative research.Qualitative data sources were obtained from 10 informants who were experts in making eel randang. Sources of quantitative data were obtained from 10 panelists who were experts on randang eel from the local community and 5 limited panelists from UNP Food and Beverage lecturers.Qualitative data collection techniques are observation,interviews, documentation andquantitative data collection techniques are organoleptic test questionnaire format.The qualitative data analysis technique uses three lines,namely:data reduction,data presentation,drawing conclusions and quantitative data analysis techniques using the formula(Mx =∑X/N).The organoleptic test of the standard recipe for randang eel is the form of randang eel(5 cm long enough),the color of the eel(blackish brown), the aroma(fragrant),the texture of the eel randang(dry enough oily),the texture of the eel randang(quite tough),the taste randang eel(seep),and taste(savory).